Use of Herbal Dietary Supplement Si-Wu-Tang and Health-Related Quality of Life in Postpartum Women: A Population-Based Correlational Study. (14th February 2013) - Chang, Pei-Jen; Lin, Ching-Chun; Chen, Yi Chun; Chuang, Chao-Hua; Tseng, Yu-Ching; Hsieh, Wu-Shiun; Lin, Shio-Jean; Chen, Pau-Chung
Abstract : Objective . The aim of the study was to explore the association between women's use of herbal dietary supplement Si-Wu-Tang during the postpartum period and their health-related quality of life. Methods . This is a population-based correlational study. We used multistage, stratified, systematic sampling to recruit 24, 200 pairs of postpartum women and newborns from the Taiwan National Birth Registry in 2005. A structured questionnaire was successfully administered to 87.8% of the sampled population. Trained interviewers performed home interviews 6 months after the women's deliveries between June 2005 and July 2006. The Medical Outcomes Study 36-item Short-Form (SF-36) was used to measure the quality of life of the women along with the frequency of Si-Wu-Tang use. Results . Si-Wu-Tang use after delivery improved women's score for bodily pain and also improved their score for mental health when used more than 10 times. In addition, there were increases in general health and vitality scores in the group who continuously used Si-Wu-Tang more than 10 times after using Sheng-Hua-Tang. Conclusion . Use of Si-Wu-Tang after delivery may be associated with women's health-related quality of life especially for those who previously used Sheng-Hua-Tang. These results are exploratory and need to be replicated.